Bariery kulturowe w transferze wiedzy w organizacjach globalnych - Rakowska, Anna (Cultural bariers in knowledge exchange in global organizations, 2006)
The aim of the article is to present the most common barriers which may occur when global companies open their business in new market, and transfer directly their business knowledge to culturally different country. Two examples were presented, first the process of transferring American management knowledge to Russia, and transfer of managerial practices by French food retailers to operations in Poland. There were described the best methods of developing managers well prepared in the global market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 408-415